Asthma and cystic fibrosis: A tangled web. Issue 3 (13th January 2014) - Kent, Brian D.; Lane, Stephen J.; van Beek, Edwin J.; Dodd, Jonathan D.; Costello, Richard W.; Tiddens, Harm A.W.M.
Summary Successfully diagnosing concomitant asthma in people with cystic fibrosis (CF) is a challenging proposition, and the utility of conventional diagnostic criteria of asthma in CF populations remains uncertain. Nonetheless, the accurate identification of individuals with CF and asthma allows appropriate tailoring of therapy, and should reduce the unnecessary use of asthma medication in broader CF cohorts. In this review, we discuss the diagnostic challenge posed by asthma in CF, both in terms of clinical evaluation, and of interpretation of pulmonary function testing and non‐invasive markers of airway inflammation. We also examine how the role of cross‐sectional thoracic imaging in CF and asthma can assist in the diagnosis of asthma in these patients. Finally, we critically appraise the evidence base behind the use of asthma medications in CF populations, with a particular focus on the use of inhaled corticosteroids and bronchodilators. As shall be discussed, the gaps in the current literature make further high‐quality research in this field imperative. Pediatr Pulmonol. 2014; 49:205–213. © 2014 Wiley Periodicals, Inc.